2020
DOI: 10.1007/s10681-020-02614-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of the common and dwarf bunt resistance gene Bt12 descending from the wheat landrace PI119333

Abstract: Common bunt (CB), caused by Tilletia caries and T. foetida, and dwarf bunt (DB), caused by T. controversa, are particularly destructive diseases of wheat grown under organic (low-input) production conditions and negatively affect both grain yield and quality. A total of 16 race specific bunt resistance genes have been proposed to date. Thereof, only Bt9 and Bt10 have been mapped so far. A mapping and two validation populations comprising 176 recombinant inbred lines were evaluated for CB and DB in artificially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 32 publications
6
31
1
Order By: Relevance
“…Blue segments and markers highlighted in bold letters in blue color refer to positions of published QTL. Numbers in brackets designate the following refences: [1] Chen et al ( 2016 ), [2] Wang et al ( 2009 ), [3] Singh et al ( 2016 ), [4] Fofana et al ( 2008 ), [5] Wang et al ( 2019 ), and [6] Muellner et al ( 2020 ) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Blue segments and markers highlighted in bold letters in blue color refer to positions of published QTL. Numbers in brackets designate the following refences: [1] Chen et al ( 2016 ), [2] Wang et al ( 2009 ), [3] Singh et al ( 2016 ), [4] Fofana et al ( 2008 ), [5] Wang et al ( 2019 ), and [6] Muellner et al ( 2020 ) …”
Section: Resultsmentioning
confidence: 99%
“…2 ), but the precise location of Bt12 is unknown as well. Bt12 has been reported to have a major impact on CB and only a minor to moderate one on DB resistance (Muellner et al 2020 ). This is in contrast to Chen et al ( 2016 ), who reported a strong effect on DB, and our finding that QBt.ifa-7DS conferred resistance to DB only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MAS and pyramiding approaches require the tagging of resistance genes by closely linked markers. Genetic mapping is an effective tool for the identification of such markers as well as for understanding inheritance and isolating disease resistance loci in plants [4,[19][20][21]. Such maps with different types of molecular markers have been developed for C. arabica, and genes and quantitative trait loci (QTLs) associated with resistance to CLR [22][23][24][25][26] and coffee berry disease (CBD) [27,28] have been mapped.…”
Section: Introductionmentioning
confidence: 99%